2017
DOI: 10.1021/acs.macromol.7b00952
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the High-Throughput Fabrication of Glycopolymer Microarrays through Thiol–Ene Chemistry

Abstract: The fabrication of microarrays consisting of well-defined glycopolymers is described. This was achieved by postfunctionalization of an immobilized poly­(allyl glycidyl ether) using unprotected thiol-modified carbohydrates through thiol–ene conjugation chemistry. This enabled the fabrication of glycopolymer microarrays in which the density and composition of the carbohydrate moieties varied along each of the polymer chains displayed across the array. These glycopolymer microarrays were applied in the evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…As a result, many new functional polymers have been explored and used in interdisciplinary fields as sensors, gene/drug carriers, antibacterial surfaces, tissue engineering scaffolds, (stem)cell factories, etc. (Akinc et al., 2003, Algahtani et al., 2014, Anderson et al., 2004, Anderson et al., 2005, Anderson et al., 2006, Bosman et al., 2001, Celiz et al., 2014, Chapman et al., 2016, Goldberg et al., 2008, Gupta et al., 2010, Hook et al., 2012, Khan et al., 2010, Lynn et al., 2001, Mao et al., 2018, Mei et al., 2010, Meier et al., 2004a, Meier et al., 2004b, Neumann et al., 2017, Ting et al., 2015, Ting et al., 2016). This has opened new research directions in polymer science and expanded the application scope of polymers beyond traditional plastics and rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many new functional polymers have been explored and used in interdisciplinary fields as sensors, gene/drug carriers, antibacterial surfaces, tissue engineering scaffolds, (stem)cell factories, etc. (Akinc et al., 2003, Algahtani et al., 2014, Anderson et al., 2004, Anderson et al., 2005, Anderson et al., 2006, Bosman et al., 2001, Celiz et al., 2014, Chapman et al., 2016, Goldberg et al., 2008, Gupta et al., 2010, Hook et al., 2012, Khan et al., 2010, Lynn et al., 2001, Mao et al., 2018, Mei et al., 2010, Meier et al., 2004a, Meier et al., 2004b, Neumann et al., 2017, Ting et al., 2015, Ting et al., 2016). This has opened new research directions in polymer science and expanded the application scope of polymers beyond traditional plastics and rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…The glycan microarray provides a powerful platform for rapid profiling of protein interactions with surface-immobilized glycans [41]. Established initially as a way to present individual glycans [42], the array concept was later expanded to include well-defined synthetic glycoconjugates, such as neo-glycoproteins [43,44], glycodendrimers [45] or glycopolymers [39,46,47], allowing for presentation of glycans in a number of modes with control over scaffold geometry, glycan valency and spacing, and surface density of glycoconjugates. Most recently, glycan arrays prepared by immobilization of glycan mixtures within individual spots revealed that the presence of neighbouring glycans may result in higher avidity antibody binding to target epitope and that both density and structure of neighbouring glycans can effect recognition (figure 3) [48,49].…”
Section: Static Surface-supported Glycocalyx Modelsmentioning
confidence: 99%
“…The Bradley group has reported the preparation of a glycopolymer library using a substrate and high-throughput analyses with lectins, showing the utility of the library method. 14…”
Section: Introductionmentioning
confidence: 99%